Impact of Information Technology: Developments the Related Research in the Last 2 Decades - Amri, Irman; Windiarti, Ika Safitri (International Journal of Engineering, Science and Information Technology, 2025)
This study outlines the potential future direction of research in information technology impact. Based on current findings, we identify key areas where further investigation is needed to advance the understanding and application of information technology. Our discussion highlights gaps in the literature, proposes new methodologies, and suggests an interdisciplinary approach to answering unsolved questions. This research highlights the significant impact of information technology in improving operational efficiency and quality in the education, health, and economic sectors over the past two decades. Using the PRISMA method for systematic literature analysis, this study identifies key trends and developments in information technology and provides recommendations for evidence-based practices and policies. The results of this study are expected to make an essential contribution to theory and practice, offering insights for more informed decision-making and more effective implementation strategies in the use of information technology.